Formulating Risk Mitigation Strategies on the Engineering, Procurement and Construction (EPC) Project in Mini Hydro Power Plant Development - Roeshardianto, Prabono; Siregar, Hermanto; Lukytawati (Jurnal Aplikasi Manajemen, 2015)
The demand for electricity in Indonesia has been escalating rapidly for the pastyears. One of the priorities to fulfill the demand is by developing mini hydro power. However,the potential risk of implementation can arise at any stages of EPC process. XYZ is a EPCcontractor company facing problems in managing risk. The objectives of this study are toidentify risks and measuring the magnitude of the risk and develop effective risk mitigationstrategies. Data analysis was conducted by determining the relative importance index (RII).There are 12 factors (22,64%) were categorized as very significant risks (80 RII 100). Therespondent considers that the level grade in reliability and availability plant are the highest riskfactor. The twelfth rank was taken by inaccuracy of engineers'estimations during the preparationof material take over (MTO)/bill of quantity (BQ). Improvement in the company's humanresources is a major concern of the respondents, because the main weight of the respondent'sassessment of the strategy group was the dominant risk factor based on analitical hyrarchyprocess (AHP).